Qualitative Analysis of Medicinal Chemical Content in Packaged Herbal Medicine: A Systematic Literature Review - Nurhamidah, Wida; Fajar Adi Prasetya; Muhamad Al Atoriq; Ali Alfarizzy (HM Publisher, 2024)
Qualitative analysis of the medicinal chemical content in packaged herbal medicine is an examination method to determine whether or not there is medicinal chemical content (BKO) in packaged herbal medicine. BKO is a chemical that is not listed in the composition of herbal medicine permitted by the Food and Drug Supervisory Agency (BPOM). The presence of BKO in packaged herbal medicine can endanger consumer health. This study aims to explore qualitative analysis methods for the content of medicinal chemicals in packaged herbal medicine. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potency of qualitative analysis of medicinal chemical content in packaged herbal medicine. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Qualitative analysis of the BKO content in packaged herbal medicine is an important method to ensure the safety of the herbal medicine consumed. Qualitative analysis of BKO content in packaged herbal medicine can be carried out using various methods, including thin layer chromatography (TLC), gas liquid chromatography (GLC), UV-vis spectrophotometry, and mass spectrophotometry (MS).